(untitled) (Revista Latino-Americana de Enfermagem, 2011)
Objective: to identify the work process, the psychic workloads and the strains generated in nursing workers. Method: the study was developed in five Brazilian university hospitals. The sample was composed by 62 nursing workers and the data collection was done by focal group technique, followed by the application of a collective inquire. The data were quantitatively described and systematized according to a thematic analysis. Results: the study population represented 35,37% of the hospital workforce in national setting. The workers mentioned are exposure to several kinds of psychic workload and link them to with others workloads, highlighting the strain processes resulting from this kind of workload, such stress, fatigue, complaints of gastritis and headaches. Conclusions: nursing workers are exposed to several workloads in the hospital environment, especially psychic workloads. This exposure starts strain processes that compromise the health and quality of life, signaling the necessity of interventions in this reality.